Trauma Registry Data Collection Practices and the Impact of Hospital Data Dictionaries: A National Survey. Issue 3 (May 2022) - Urban, Shane; Carmichael, Heather; Vasilatos, Angela; Moe, Martin; Dumond, Robbie; Kennard, Lori; Vega, Stephanie; Krell, Regina; Cripps, Michael W.; Velopulos, Catherine
Abstract : BACKGROUND: Trauma programs are required to collect a uniform set of trauma variables and submit data to regional, state, and or national registries. Programs may also collect unique data elements to support hospital-specific initiatives. OBJECTIVE: This study explored what additional data elements are being collected by U.S. trauma programs and the impact of having a hospital-specific data dictionary. METHODS: An anonymous, cross-sectional survey exploring what additional data are being collected, and the impact of having a hospital-specific data dictionary, was distributed by the Society of Trauma Nurses, Trauma System News, and the American College of Surgeons. The survey was open from July 2020 to September, 2020. RESULTS: There were 693 respondents from approximately 368 Level I/II trauma programs. The estimated trauma center response rate was 59.4% ( n = 368/620). Level I programs had a higher response rate than Level II programs (66.9% and 53.4%, respectively). In our sample, 85.5% of responding centers collect additional data. The most common additional data collected at Level I/II programs concerned quality improvement initiatives (70.3% and 66.1%, respectively). Other commonly collected data pertained to deaths (60.6%) and complications (50.3%). Only 43% of responding centers ( n = 161/368) have a hospital-specific data dictionary. Hospitals that collect additional data were more likely to have such a resource compared with those that do not ( n = 147/315, 46.7% vs. n = 14/53, 26.4%, p = .01). CONCLUSION: Most trauma programs collect data outside required fields. Fewer than half define these data in a data dictionary. Centers should consider establishing a data dictionary to define data collected.